Healthy Dating Education Socialization to Adolescents at SMPN Alok, Sikka District - Sitti Anggraini; Maria Mensiana Kerona (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Dating behavior in today's teenagers has led to unhealthy dating behavior. Unhealthy courtship will have an impact on pregnancies outside of marriage, early marriage, school dropouts, and cause sexually transmitted diseases. The purpose of holding community service is to provide educational socialization about healthy dating behavior for adolescents at SMPN Alok Maumere. The methods or approaches used in this community service are a) Preliminary observation & interview methods, b) Coordination with the school, c) Implementation of socialization of healthy dating education for adolescents accompanied by pre tests and post tests d) Evaluation. The results showed that there was an increase in knowledge about healthy courtship in adolescents.